INTERACTIVE 3D SYSTEMS OF VIRTUAL REALITY AS ONE OF THE DIRECTIONS FOR EVOLUTION OF DISTANCE LEARNING TECHNOLOGIES IN HIGHER SCOOL - D V Senashenko (RUDN Journal of Informatization in Education, 2016)
The article describes history of 3D virtual interactive technology developing and gives story of it’s using for different business companies and universities. Statistical analysis of target audience is provided. Features of such systems are described. Particularly author mentions functionality and advantages of 3D-systmes as one of long-term distant learning technology during educational program realization and formulates arguments for introduction of this technology to distant education systems of Russian Higher school. Discusses usability of it for distance learning in high school.